EFFECT OF FAMILY PSYCHOEDUCATION ON CAREGIVER SUPPORT IN THE TREATMENT OF PATIENTS WITH TYPE II DIABETES MELLITUS - Andika Siswoaribowo; Mateus Sakundarno; Muhammad Mu’in (Belitung Raya Foundation, Indonesia, 2018)
Background: Diabetes Mellitus is a chronic disease that requires treatment for long periods of time so it can cause physical and psychological problems for sufferers and families (caregiver). Caregiver's role is expected to provide support for people with diabetes mellitus. Family psychoeducation is a strategy that can be applied for caregiver in overcoming problems that arise during the treatment of patients with diabetes mellitus. Objective: This study aims to determine the effect of family psychoeducation on caregiver support in the treatment of patients with type II diabetes mellitus. Methods: This research used a quasi-experiment with pre-test post-test control group design. A total of 46 caregivers and patients with diabetes mellitus were recruited purposively, with 23 respondents assigned in the experiment and control group. Caregiver support scale was used to measure caregiver support, and Hensarling Diabetes Family Support Scale (HDFSS) for measuring perception of patients toward the treatment of caregiver. Data were analyzed using paired t-test and independent t-test. Results: Findings showed there was an increase of caregiver knowledge from 5.39 to 9.09 and an improvement of caregiver treatment from 40.30 to 67.04 after given family psychoeducation. There was a significant difference of caregiver support in the experimental and control group with p-value <0.001 (<0.05). Conclusion: Family psychoeducation can increase caregiver support in the treatment of diabetes mellitus patients. The intervention can be one of nurses’ interventions in the empowerment of family in improving the treatment of chronic diseases, particularly in diabetes mellitus.